Process-based vegetative growth model for cereal rye winter cover crop using object-oriented programming and linked-list data structure - Wang, Zhuangji; Timlin, Dennis; Thapa, Resham; Fleisher, David; Beegum, Sahila; Han, Eunjin; Schomberg, Harry; Mirsky, Steven; Sun, Wenguang; Reddy, Vangimalla; Horton, Robert; Tully, Katherine (Computers and electronics in agriculture, 2025)
•A cereal rye cover crop model is developed using object-oriented programming.•Organs are assembled based on a tiller hierarchy as the entire plant architecture.•The “representative plant” bridges individual and field-scale plant morphology. Cereal rye (Secale cereale L.) has been extensively studied as a winter cover crop in conservation agriculture using experimental and modeling approaches. Previous studies generally modeled cereal rye by modifying existing cash crop models. This study aims to develop a new cereal rye vegetative growth model and evaluate model accuracy. The new model, namely RYESIM, employs object-oriented programming techniques and a linked-list data structure to present the emergence order of cereal rye organs, such as leaves, internodes, and tillers. Individual organs are abstracted as “classes,” which encapsulate organs’ morphological features and emergence-growth-senescence processes as member variables and functions. Multiple organs are assembled based on the tiller hierarchy to formulate the cereal rye plant architecture. RYESIM also contains “representative plant” as an average process among multiple individual plants, which bridges individual organs’ growth and field-scale averaged plant morphology, as well as ensuring plant-level biomass and nitrogen (N) mass balance. Existing soil (2DSOIL) and biochemical photosynthesis models are incorporated to estimate soil water-nutrient supply, carbon assimilation and transpiration. RYESIM was evaluated using published field data measured in the Mid-Atlantic region of the USA. Compared to observed values, the relative mean absolute errors of RYESIM for tiller number, aboveground biomass and N mass were within 0.3, 0.4 and 0.5 (with exceptions), and the RYESIM simulated values fell within the value ranges from literature results. Therefore, RYESIM provides effective simulations on cereal rye vegetative growth, and the RYESIM model structure also provides a paradigm for future “multi-tiller” cash crop model development.